Subsurface mapping of the Ross Island flexural basin, southwest Antarctica - Wenman, Christopher P., author; Harry, Dennis, advisor; Egenhoff, Sven, committee member; Gooseff, Mike, committee member (Colorado State University. Libraries, 2016)
Ross Island is a post-Miocene (< 4.6 Ma) volcanic island located in the Ross Sea region of southwest Antarctica. This region of Antarctica borders the western edge of the West Antarctic Rift System, along the Transantarctic Mountain front. Marine and over-ice multi-channel seismic reflection surveys and borehole studies targeting the Ross Sea region over the last 30+ years have been used in this study to develop a seismic stratigraphic model of the development and evolution of the Ross Island flexural basin. Four key stratigraphic horizons were identified and mapped to fully capture the basin-fill, as well as strata lying above and below the flexural basin. From oldest to youngest these horizons are named RIB-m, RIM-g, RIM-b and RIB-r. Time structure, isochron and isochore maps were created for the horizons and the stratigraphic intervals they bound. The seismic stratigraphic record shows the Ross Island flexural moat formation post-dates the main tectonic subsidence phase within the Victoria Land Basin. The maps presented here are the first to fully illustrate the evolution of the Ross Island flexural basin. The maps highlight depositional patterns of two distinct periods of flexural subsidence and basin-filling superimposed on the older N-S trending Victoria Land Basin depocenter. Two units of flexural basin fill, Unit FFI between horizons RIM-g and RIM-b (the oldest flexural basin fill), and Unit FFII between horizons RIM-b and RIB-r (the youngest flexural basin fill) are associated with the two periods of flexural subsidence. Flexural moat subsidence and subsequent filling occurred episodically during periods of active volcanism on the island. Unit FFI is estimated to range from ca. 4 to 2 Ma, corresponding with formation of the Mt. Bird volcanic edifice on Ross Island. Unit FFII ranges in age from ca. 2 to 1 Ma, and is related to Mt. Terror, Mt. Erebus, and Hut Point Peninsula volcanism. The isochore maps suggest the depocenter of the flexural basin during both time intervals was located north of the island, instead of directly beneath the Ross Island topographic load. Factors contributing to the northerly location of the depocenter include i) volcanic loading by McMurdo Volcanic Group subsea volcanic features north of the island, ii) partial compensation of the main Ross Island load by low-density, partially molten rock beneath the island, iii) extensional faulting within the Terror Rift, and iv) seaward-thickening shelf sediments transported from the Ross Ice Shelf. The seismic data show that the onset of filling of the flexural moat around Ross Island coincided with the end of ice grounding events in the area. We infer that this was caused by flexural subsidence of the seafloor to accommodate the Ross Island load.